Developing countries and UNCTAD (United Nations Conference on Trade and Development). - Shah, Manubhai (Bombay: Vora & Co., Publishers PVT. Ltd., 1968)
This volume examines the relationship between developing countries and the United Nations Conference on Trade and Development.
lje 25/1/19
Loans
Keywords: United Nations; Developing countries; Trade